2010
DOI: 10.3109/0886022x.2010.510615
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime hospital blood pressure – a predictor of death, ESRD, and decline in GFR

Abstract: Nighttime systolic blood pressure (BP) from ambulatory blood pressure monitoring (ABPM) is more predictive than clinic BP for cardiovascular disease, stroke, and death even after controlling for clinic BP. However, ABPM is expensive and burdensome to obtain regularly. BPs obtained in the hospital may provide a window into nighttime BP. We conducted a retrospective cohort study of all hypertensive patients admitted to the Cleveland VAMC in 2002 and 2003 with one or more BP recorded between midnight and 6am on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…16,19 Persons who do not exhibit a 10% to 20% decrease in blood pressure at night (compared to day) are classified as “nondippersȍ nondipping is associated with an increased risk of chronic kidney disease. 16,32 Nikolaeva and colleagues 33 found that the circadian timing system controls the daily rhythms of sodium and potassium excretion by the kidney, which suggests that dysfunction of these rhythms may have a significant influence on blood pressure. A longitudinal study showed that creatinine clearance declines more rapidly in nondippers than in dippers, and urinary protein excretion is greater in the nondippers than in the dippers.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 Persons who do not exhibit a 10% to 20% decrease in blood pressure at night (compared to day) are classified as “nondippersȍ nondipping is associated with an increased risk of chronic kidney disease. 16,32 Nikolaeva and colleagues 33 found that the circadian timing system controls the daily rhythms of sodium and potassium excretion by the kidney, which suggests that dysfunction of these rhythms may have a significant influence on blood pressure. A longitudinal study showed that creatinine clearance declines more rapidly in nondippers than in dippers, and urinary protein excretion is greater in the nondippers than in the dippers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who ultimately developed microalbuminuria had a rise in nighttime BP between the baseline and year 2 ambulatory BP; nighttime BP did not change in those who did not develop microalbuminuria. In a novel approach to evaluating nighttime BP, our group looked at hospitalized patients who had BP measured at night; higher nighttime BP was associated with higher risk for subsequent adverse clinical outcomes [40]. In summary, alteration in diurnal variation with elevation in nocturnal BP is common in CKD and is associated with higher risk of renal and cardiovascular outcomes.…”
Section: Altered Diurnal Rhythm In Ckd: Causes and Implicationsmentioning
confidence: 98%
“…In total, 266 subjects died, 22 developed ESRD, 99 had a 50% decline in GFR, and 136 developed MI. Moreover, the results showed that the adjusted hazard ratios associated with a 10 mmHg increase in nighttime systolic BP were 1.04 (95% CI, 0.93 to 1.16) for death, 1.31 (0.95 to 1.80) for ESRD, 1.26 (1.08 to 1.47) for a 50% decline in GFR, 1.07 (0.92 to 1.23) for MI, and 1.12 (1.03 to 1.23) for a composite of death, ESRD, or a 50% decline in GFR [32]. After the follow-up period (median 10.7 years) for 8711 individuals, the results revealed that isolated nocturnal hypertension (normal clinic blood pressure but nocturnal hypertension) was an independent risk factor for all cause mortality and cardiovascular events [41].…”
Section: Discussionmentioning
confidence: 99%
“…Non-dipping status or nocturnal hypertension was associated with target organ damage and increased cardiovascular disease (CVD) risk [4,31,32,33,34,35,36,37,38,39,40]. Nighttime systolic blood pressure ≥125 mmHg may increase the incidence of cardiovascular events (HR = 2.52, 95% CI 1.77-9.02) and end-stage renal disease (HR = 1.87, 95% CI 1.41-4.57) [1].…”
Section: Discussionmentioning
confidence: 99%